(untitled) (Sociologisk Forskning, 1998)
Faith and facts in the debate on Sweden’s economic performance: the problem of objectivity in the social sciences illustrated When social scientists enter the public debate as policy experts, they are confronted with problems of objectivity discussed a generation ago by Gunnar Myrdal. Problems of objectivity are likely to be especially severe in areas related to distributive conflicts. Here the balance between politics and markets cannot be seen as only aquestion of economic efficiency but is also of relevance for distributive outcomes. In Sweden prominent economists have long argued that the ”Swedish Model” of high taxes and a large public sector has made Sweden lag behind other comparable countries in terms of GDP growth since 1970. Their arguments have been widely accepted by leading policy makers and the media. The empirical bases for this claim are examined and found seriously wanting, a situation illustrating problems of social science objectivity long ignored in the sociology of science.